Vasculitides associated with IgG antineutrophil cytoplasmic autoantibodies in childhood - Vanoni, Federica; Bettinelli, Alberto; Keller, Franco; Bianchetti, Mario G.; Simonetti, Giacomo D. (Pediatric nephrology, 2010)
Immunoglobulin (Ig)G antineutrophil cytoplasmic autoantibodies are causally associated with necrotizing vasculitides that are characterized immunopathologically by little or no deposition of immunoreactants, such as Wegener granulomatosis, microscopic polyangiitis, Churg-Strauss angiitis, "renal-limited" vasculitis and a number of drug-induced vasculitides. Clinical routine testing targets the antigens myeloperoxidase and proteinase 3. However, in all of the conditions mentioned, the renal histopathologic findings are indistinguishable. Churg-Strauss angiitis (characterized by necrotizing vasculitis, granulomatous inflammation and tissue eosinophilia), Wegener granulomatosis (characterized by necrotizing vasculitis and granulomatous inflammation) and microscopic polyangiitis (characterized by necrotizing vasculitis) often present with fever, weight loss and a multisystem involvement (ear, nose, throat, lung, eyes, peripheral nerve and heart). Fifty years ago these conditions were very often fatal within 6 months of diagnosis. The introduction of corticosteroids and cyclophosphamide has resulted in a dramatic clinical benefit. Patients who develop treatment-related morbidity can be switched from cyclophosphamide to azathioprine after achieving remission. In patients with less severe disease, methotrexate achieves remission with a success rate similar to that of cyclophosphamide. Plasma exchange, in association with immunosuppression, is likely to be a beneficial therapy for patients with severe kidney disease or pulmonary hemorrhage.